Assessing the impact of 4-oxo-2-nonenal on lactate dehydrogenase activity and myoglobin redox stability. (October 2021) - Gonzales, Samuel A.; Pegg, Ronald B.; Singh, Rakesh K.; Mohan, Anand
Abstract: Lipid oxidation products, like α, β -unsaturated aldehydes, can react with proteins and influence meat quality. Two such key end products are 4-hydroxy-2-nonenal (4-HNE) and 4-oxo-2-nonenal (4-ONE). These compounds are far more stable than the lipid hydroperoxides from which they form; so, they can diffuse from the site of generation and cause extensive cellular damage and oxidative pathology. Glycolytic enzymes involved in the reduction of metmyoglobin (e.g., lactate dehydrogenase) are highly reactive with 4-HNE, and subsequently become less functional. Other aldehydes, such as 4-ONE, are more reactive than 4-HNE with certain functional groups/moieties including mercapto groups and arginine residues of glycolytic enzymes. Yet, little research has considered the influence of 4-ONE on an in-vitro meat model system. Findings from this study establish that 4-ONE causes loss of lactate dehydrogenase activity compared to 4-HNE at similar effective concentrations. Myoglobin, when incubated with 4-ONE, exhibited a loss in its redox stability at pH 5.8. Both 4-HNE and 4-ONE were found to be potent covalent modifiers of myoglobin, disrupting functional and structural morphology of bovine heart mitochondria. This study reveals that 4-ONE is a novel and highly toxic chemical species, which causes damage to mitochondrial structure and impairment of myoglobin's redox stability. Highlights: Lipid peroxidation products react with the proteins that influence myoglobin stability. 4-oxo-2-nonenal (4-ONE) cause oxidative cellular pathology in skeletal muscle. 4-ONE reactivity caused loss of lactate dehydrogenase enzymatic activity. When incubated with myoglobin, 4-ONE caused loss of redox stability of myoglobin. 4-ONE is a novel but highly toxic specie causing damage of mitochondrial structure and functions.